Application of Grain Storage System based on Strategic Planning and Modern Techniques - Lakhoua Najeh (Journal of Innovation and Applied Technology, 2019)
After a presentation of the management process of a grain silo, we present the necessity of the analysis and the identification of information in a grain silo wile using a strategic planning based on the OOPP method (Objectives Oriented Project Planning). This kind of analysis leads to an efficient management of the activities of grain silo. In fact, the OOPP method constitutes a tool of a global systemic modeling enabling to analyze a complex situation by a hierarchically decomposition until reaching an elementary level allowing to an operational planning.